"Because nobody likes Chinese girls": Intersecting identities and emotional experiences of subordination and resistance in school life. (August 2015) - Haavind, Hanne; Thorne, Barrie; Hollway, Wendy; Magnusson, Eva
How do emotions enter into children's negotiated understandings and situated uses of categories of identity? This question guided a revisit to an ethnographic study of a multi-cultural context in Oakland, California. A focus group discussion among four Chinese American girls just graduating from elementary school and an interviewer, also Chinese American, was chosen for closer study. This secondary analysis focuses on how the girls engaged in school events and how in the interview they shared experiences of being excluded and rejected by peers. Thus, both reports about life in school and lived life in the group discussion were analyzed in ways that followed the girls' individual and collective emotional dynamics. Emotional tension between using and being used by categories drove their stories about belonging, exclusion and subordination, and resistance. The girls' handling of social identities in relation to language use, required activities, and girly appearance in school demonstrated how they were able to draw on an eclectic and intersecting mix of categories. In the containing setting of the focus group, the girls processed their raw emotional experience of being taunted and humiliated. In the process they could challenge and destabilize the meanings attached to the categories of identity used against them. Therefore, intersectional analyses cannot take any specific meanings of social categories such as gender, ethnicity/race, and age, as the starting points. Rather, in each specific instance, the meanings of social categories will emerge as the results of the analysis.